State of the Art in the Treatment of Systemic Vasculitides - Luqmani, Raashid Ahmed (Frontiers in Immunology, 2014)
Anti-neutrophil cytoplasm antibodies (ANCA) are associated with small vessel vasculitides (AASV) affecting the lungs and kidneys. Structured clinical assessment using the Birmingham Vasculitis Activity Score and Vasculitis Damage Index should form the basis of a treatment plan and be used to document progress, including relapse. Severe disease with organ or life threatening manifestations needs cyclophosphamide or rituximab, plus high dose glucocorticoids, followed by lower dose steroid plus azathioprine or methotrexate. Additional plasmapheresis is effective for very severe disease, reducing dialysis dependence from 60% to 40% in the first year, but with no effect on mortality or long term renal function, probably due to established renal damage. In milder forms of ANCA associated vasculitis, methotrexate, leflunomide or mycophenolate mofetil are effective. Mortality depends on initial severity: 25% in patients with renal failure or severe lung haemorrhage; 6% for generalised non-life threatening AASV but rising to 30-40% at 5 years. Mortality from GPA is 4 times higher than the background population. Early deaths are due to active vasculitis and infection. Subsequent deaths are more often due to cardiovascular events, infection and cancer. We need to improve the long term outcome, by controlling disease activity but also preventing damage and drug toxicity. By contrast, in large vessel vasculitis where mortality is much less but morbidity potentiallly greater, such as giant cell arteritis and Takayasu arteritis, therapeutic options are limited. High dose glucocorticoid results in significant toxicity in over 80%. Advances in understanding the biology of the vasculitides are improving therapies. Novel, mechanism based therapies such as rituximab in AASV, mepolizumab in eosinophilic granulomatosis with polyangiitis and tocilizumab in GCA, but the lack of reliable biomarkers remains a challenge to progress in these chronic relapsing diseases.